2021
DOI: 10.3390/atmos12111521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Prototype Broadband Water-Vapour Profiling Differential Absorption Lidar at Cardington, UK

Abstract: For a one-month period in summer 2020, a prototype Vaisala broadband differential absorption lidar (BB-DIAL) was deployed at a Met Office research site. It was compared with in-situ observations of humidity (93 radiosonde ascents and 27 of uncrewed aerial vehicle flights) and the Met Office 1.5 km resolution numerical weather prediction (NWP) model: UK Variable resolution model (UKV). The BB-DIAL was able to collect data up to the cloud base, in all-weather situations including rain, when it was possible to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The Raman LiDAR presented comparable results with a slightly higher uncertainty estimated at 9.2%. Using a similar technique, Gaffard et al [49] evaluated a Dial LiDAR and reported an uncertainty between 5% and 10%, suggesting similar performances. When comparing the Meteodrone to the Raman LiDAR, similar results were obtained with an RMS of 9.02%.…”
Section: Wmo Requirementsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Raman LiDAR presented comparable results with a slightly higher uncertainty estimated at 9.2%. Using a similar technique, Gaffard et al [49] evaluated a Dial LiDAR and reported an uncertainty between 5% and 10%, suggesting similar performances. When comparing the Meteodrone to the Raman LiDAR, similar results were obtained with an RMS of 9.02%.…”
Section: Wmo Requirementsmentioning
confidence: 96%
“…These WMO requirements were recently used by Gaffard et al [49] to evaluate novel measurements like a DIAL LiDAR. This study aims to evaluate whether Meteodrones fulfill these requirements.…”
Section: Wmo Requirements and Quality Analysismentioning
confidence: 99%
“…The DIAL underwent initial testing in Helsinki and Toronto before being deployed to Iqaluit (Mariani et al, 2020b). This new system and its predecessor were extensively evaluated in different climates and demonstrated excellent agreement with independent water vapour profile observations from co-located radiosondes, radiometers, UAV's, and Raman lidars (Newsom et al, 2020;Gaffard et al, 2021).…”
Section: Dial and Raman Water Vapour Lidarsmentioning
confidence: 99%
“…Consequently, we have removed this altitude region from our diurnal analysis. Most recently, Gaffard et al (2021) conducted a 1 month validation of a second preproduction version at the UK Met Office testing site in Cardington. They found biases of similar range and magnitude to the previous studies.…”
Section: Vaisala Differential Absorption Lidarmentioning
confidence: 99%
“…In this study, we address both the need for higher vertical resolution and higher latitude observations of water vapour profiles. In 2018, Environment and Climate Change Canada (ECCC) deployed a preproduction Vaisala lidar (Mariani et al, 2020; Newsom et al, 2020; Gaffard et al, 2021; Mariani et al, 2021) and installed it at the Iqaluit, Nunavut supersite (Joe et al, 2020). The lidar is a differential absorption lidar (DIAL) capable of producing specific humidity profiles from 90 m to 3 km altitude above ground level (depending on the meteorological conditions) at 100–300 m vertical resolution (in the first 1.5 km altitude) at a temporal frequency of 20 min.…”
Section: Introductionmentioning
confidence: 99%